Domain-Specific Analysis Of Emotional Intelligence Quotient Among Medical Professionals: A Cross-Sectional Study From Perambalur, Tamil Nadu - Thirunavukkarasu, Sriranganathan; Sugumaran, Sukanya; Muniyapillai, Tamilarasan; venkateshvaran, Sriandaal (Journal of Neonatal Surgery, 2025)
Background and Objective: Emotional intelligence represents a critical competency for healthcare professionals, potentially superseding traditional intelligence metrics in determining clinical efficacy. While emotional intelligence has been extensively studied in various professional contexts, limited research has examined its domain-specific distribution among medical practitioners in South India. This study aimed to estimate the emotional intelligence quotient among medical professionals in Perambalur, Tamil Nadu, with specific attention to emotional sensitivity, emotional maturity, and emotional competency domains. Methodology: A cross-sectional study was conducted among 125 medical professionals in Perambalur district, Tamil Nadu, during July-August 2018. Participants were recruited through convenience sampling. Data were collected using a validated 22-item questionnaire (Emotional Quotient Test by Singh D and Chadha NK) measuring three domains: emotional sensitivity (score range: 25-100), emotional maturity (35-140), and emotional competency (50-200). Sociodemographic information was recorded. Data were analysed using descriptive statistics and chi-square tests to examine associations between emotional intelligence domains and demographic variables. Results: The study population comprised 58 males (46.4%) and 67 females (53.6%), with the predominant age group being 26-30 years representing 56 participants (44.8%). Domain-specific analysis revealed significant heterogeneity in emotional intelligence distribution (χ²=197.63, p<0.001). Emotional competency demonstrated the highest scores, with 112 participants achieving "Extremely High EQ" (89.6%), while emotional maturity showed concerning deficits with only 5 participants in the "Extremely High EQ" category (4.0%) and 42 participants classified as "Low EQ" (33.6%). Age-stratified analysis revealed a significant association between age and emotional competency (χ²=9.07, p=0.028), with progressive improvement across age cohorts culminating in 100% "Extremely High EQ" classification in the 31-35 and 36-40 year groups. No significant gender differences were observed across any emotional intelligence domain. Conclusion: Medical professionals demonstrated substantial domain-specific variation in emotional intelligence profiles, with pronounced strength in emotional competency and concerning deficits in emotional maturity. The significant association between age and emotional competency suggests experiential enhancement of this domain through clinical practice. These findings highlight the need for targeted educational interventions focused on emotional maturity development throughout medical training and professional development programs.